Green-solvent-processable organic solar cells. Issue 9 (November 2016) - Zhang, Shaoqing; Ye, Long; Zhang, Hao; Hou, Jianhui
Abstract : Solution-processable organic photovoltaics (OPV) has emerged as a promising clean energy-generating technology due to its potential for low-cost manufacturing with a high power/weight ratio. The state-of-the-art OPV devices are processed by hazardous halogenated solvents. Fabricating high-efficiency OPV devices using greener solvents is a necessary step toward their eventual commercialization. In this review, recent research efforts and advances in green-solvent-processable OPVs are summarized, and two basic strategies including material design and solvent selection of light-harvesting layers are discussed. In particular, the most recent green-solvent-processable OPVs with high efficiencies in excess of 9% are highlighted.